EFL Learners Experiences in Using Real Life Application to Improve English Speaking Skills - Rena Dwi Indra Suwandana; Muhammad Hifdil Islam; Zainuddin (Linguistic, English Education and Art (LEEA) Journal, 2026)
This study sought to investigate EFL learners' experiences with real-life apps and their impact on English speaking ability. This study used a descriptive qualitative method with four seventh-semester English Education Department students who actively used real-world applications for speaking practice. Semi-structured interviews and observations were used to collect the data, which was then analysed thematically. The findings demonstrated that real-life applications helped learners improve their speaking skills by providing authentic communication experiences, flexible learning options, and interactive speaking practice. The programmes improved learners' pronunciation, vocabulary knowledge, fluency, and communication confidence through continual speaking exposure and meaningful interaction. Furthermore, the findings revealed that real-life applications decreased speaking fear and encouraged students to participate more actively in communication events. The study concludes that real-life applications can be effective tools for improving English speaking skills in EFL learners because they foster communicative, learner-centered, and authentic learning environments that support both linguistic and psychological aspects of speaking development. Keywords: Authentic Communication, EFL Learners, English Learning, Real-life Applications, Speaking Skills